Facies analysis and depositional framework of Late Permian-Jurassic sedimentary successions, Western Salt Range, Pakistan: implications for sequence stratigraphic trends and paleogeography of the Neo-Tethys Sea - Abdul Basit; Prof. Muhammad Umar; Muhammad Jamil; Muhammad Qasim (Kuwait Journal of Science)
Facies analysis and T-R sequence stratigraphic approach of Late Permian to Jurassic sedimentary units in Western Salt Range, Pakistan were accomplished to construe the depositional environments and basin evolution. The analysis affirms the rendition of sequence stratigraphic trends and paleogeography of first megasequence phase of Neo-Tethys Sea. Sedimentological contingents, T-R sequence stratigraphic framework and sea level curve of the strata argue active tectonic’s effects on sedimentation. During Late Permian, the rift related magmatic activities deceased, which imparted to the onset of transgression and deposition of shelf carbonates with retrogradational (transgressive) parasequence sets in Wargal Formation. Respective rifting and tectonic uplift events induced the sea level fall ascertaining the onset of terrigenous shelves and deltaic successions in terminal Permian and Early-Mid Triassic with an enlighten switch from agradational to progradational parasequence sets (regressive parasequences) in Chhidru, Mianwali and Tredian formations. The closure of Paleo-Tethys and emergence of semi-arid hot tropical climate throughout Late-Triassic, led the onset of tidal-lagoonal environments and deposition of retrogradational (transgressive) parasequence sets in Kingriali Formation. During Early Jurassic, a well-known northward drift of Pangaea ensued in global cooling and increased humidity, which consequently stimulated clastic-carbonate sedimentation of Datta and Samana Suk formations with progradational and retrogradational parasequence sets respectively.